FROM PRIVATE CUSTODY TO PUBLIC POLICY: THE POLITICS OF STATE RESPONSIBILITY FOR POST-DIVORCE ABANDONED CHILDREN (HADHANAH) IN SERANG, INDONESIA - Faisal, Ali; Tarihoran, Naf’an; Syafuri, B; Ma’rifah, Nurul (JWP (Jurnal Wacana Politik), 2026)
This article examines how hadhanah (child custody and care) can be reframed from a private family matter into a public policy issue, positioning the state as a responsible actor when children become abandoned after divorce. Drawing on a normative–juridical and qualitative socio-legal analysis of Islamic family law, national legislation, and municipal policy instruments, the study uses Serang City as an illustrative case of policy urgency. The findings demonstrate a systematic implementation gap between Indonesia’s constitutional mandate to care for abandoned children and local-level governance practice: (1) a legal–administrative gap, where court-based custody decisions and parental obligations do not automatically trigger social welfare interventions; (2) an institutional coordination gap, marked by fragmented responsibilities among courts, social services, and child-protection agencies; and (3) a service continuity gap, in which protection responses remain reactive and episodic rather than sustained and rights-based. Based on municipal administrative data and policy documents, Serang’s 2024 records identify 12,949 abandoned children, indicating a governance problem that requires an integrated response. The paper contributes to debates on post-divorce custody by demonstrating that when hadhanah is treated solely as a private legal dispute, accountability diffuses and child protection becomes episodic; therefore, custody governance must be redesigned so the state can, within defined limits, function as an accountable guardian-like actor through coordinated local child-protection services.